Transgene-free genome editing in citrus and poplar meristem tissues via biolistic ribonucleoprotein delivery of CRISPR-Cas9 - Dhiôvanna Corrêia Rocha; Miracle Osazee Omoregbee; Weifeng Luo; Hong Fang; Qiushi Ye; Yanxin Liu; Gen Li; Juliet Mascoveto; Alessandra Alves de Souza; Gary Coleman; James N. Culver; Yiping Qi (Plant Cell Reports, 2026)
Key message Biolistic particle bombardment was used to deliver CRISPR-Cas9 ribonucleoprotein complexes (RNP) into the shoot apical meristem tissue of citrus and axillary meristem tissue of poplar, generating directed mutations in target genes. Abstract The use of meristematic tissues offers a strategic approach to genome editing in woody species, especially those that are recalcitrant to conventional tissue culture, as these regions contain totipotent, highly regenerative cells capable of giving rise to whole plants. Here, we employed biolistic delivery of genome-editing reagents into theshoot apical meristem (SAM) of citrus and the axillary meristems (AXM) of poplar. The system was first validated using a GFP expression construct and subsequently applied for targeted genome editing. In citrus, edited plants were obtained at the CsNPR3 locus exclusively through the delivery of CRISPR/Cas9 ribonucleoproteins (RNPs), whereas plasmid-based vectors were unsuccessful. Similarly, genome editing in poplar was achieved using RNPs targeting the Pt4CL1 gene. Although chimeric events were detected, this approach provides a feasible and innovative framework for producing transgene-free edited perennial plants.